REVIEW: NATURAL BIOACTIVE COMPOUNDS POTENTIAL ON INHIBITION OF TRANSMEMBRANE SERINE PROTEASE 2 WITH STRUCTURE-BASED VIRTUAL SCREENING METHOD - Haviani Rizka Nurcahyaningtyas; Masteria Yunovilsa Putra; Arry Yanuar (Medical Sains : Jurnal Ilmiah Kefarmasian, 2023)
The COVID-19 pandemic has led to a global health emergency. Suitable medications are required to prevent severe SARS-CoV-2 infection. Human transmembrane serine protease 2, which is required for viral entry into the host cells, was identified as the target protein. The present study was designed to synthesize, through a systematic review, evidence of phytochemicals found in plants that can inhibit transmembrane serine protease 2 in silico. The databases ScienceDirect, PubMed, Scopus, Nature, and SpringerLink were used for systematic exploration. Among the 113 studies retrieved, 11 were selected for the entire read and 7 studies were deemed appropriate for the qualitative synthesis. Flavonoids, including the bioactive substances luteolin, vicenin 2, naringin, 8-geranylapigenin, phenylethyl-D-rutinoside morusin, sanggenol L, and kaempferol, are the most widely studied classes of secondary metabolites. Other classes that were also evaluated were lactones, terpenoids, and saponins with withanoside-V, 11-hydroxy-2-(3,4-dihydroxybenzoyloxy)abieta-5,7,9(11),13-tetraene-12- one, and licorice as active substances, respectively. This review indicates the most bioactive components of each group of metabolites that demonstrated the greatest binding affinity for the transmembrane serine protease 2 receptor, as an initial point for selecting substances and exploring additional laboratoryÂ research and clinical studies to identify novel medication candidates for COVID-19 treatment. Â Keywords: Secondary metabolite, SARS-CoV-2, structure-based virtual screening, transmembrane serine protease 2, Plants